WILL SUPREME COURT FACE ‘A BRIDGE TOO FAR’? - Weiss, Debra Cassens (ABA journal, 2017)
Civil rights advocates who are worried about the outcome of pending blockbuster cases before the U.S. Supreme Court can take heart. If rights continue to be diluted by court decisions, "eventually, you get to a bridge too far," says retired U.S. District Judge Nancy Gertner.